2008
DOI: 10.1016/s1875-9572(08)60017-0
|View full text |Cite
|
Sign up to set email alerts
|

Infusion of Human Umbilical Cord Blood Cells Ameliorates Hind Limb Dysfunction in Experimental Spinal Cord Injury through Anti-inflammatory, Vasculogenic and Neurotrophic Mechanisms

Abstract: Our results demonstrate that HUCBC therapy may be beneficial for the recovery of SCI-induced hind limb dysfunction by increasing serum levels of IL-10, VEGF and GDNF in SCI rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 29 publications
1
34
0
1
Order By: Relevance
“…18 In addition, neurological disorders such as trauma, stroke and neurodegenerative diseases may represent another target for cell-based regenerative medicine using HUCB-derived cells. The therapeutic potential of whole HUCB and derived mononuclear cells (MNCs) in neurological disorders was investigated in animal models of central nervous system damage induced by hemorrhagic brain injury, 19 heatstroke, 20 middle cerebral artery occlusion stroke model, 21 spinal cord injury, 22 as well as TBI. 23 Given the fact that mesenchymal stem cells (MSCs) are frequently used for cell therapy of neurodegenerative disorders in clinical trials, 8,24 a recent study demonstrated the efficacy of HUCBderived MSCs in protecting mice brains after trauma.…”
Section: Introductionmentioning
confidence: 99%
“…18 In addition, neurological disorders such as trauma, stroke and neurodegenerative diseases may represent another target for cell-based regenerative medicine using HUCB-derived cells. The therapeutic potential of whole HUCB and derived mononuclear cells (MNCs) in neurological disorders was investigated in animal models of central nervous system damage induced by hemorrhagic brain injury, 19 heatstroke, 20 middle cerebral artery occlusion stroke model, 21 spinal cord injury, 22 as well as TBI. 23 Given the fact that mesenchymal stem cells (MSCs) are frequently used for cell therapy of neurodegenerative disorders in clinical trials, 8,24 a recent study demonstrated the efficacy of HUCBderived MSCs in protecting mice brains after trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Kao et al [78] , suggested that hUCB derived-CD34 + cells can induce angiogenesis and endo/exogenous neurogenesis in SCI. In addition, Chen et al [79] recently showed that hUCB stem cells have the ability to secrete multiple neurotrophic factors. Their study demonstrated an elevation of neuroprotective cytokine serum IL-10 levels and a decrease in TNF-α levels after hUCB stem cells infusion.…”
Section: Human Umbilical Cord Blood-derived Mscsmentioning
confidence: 99%
“…показали, [61]. Неврологическое улучше-ние при трансплантации МНК пуповинной кро-ви продемонстрировано также в моделях трав-мы головного и спинного мозга [7,44], детского церебрального паралича (ДЦП) [53], болезни Альцгеймера [14] и бокового амиотрофического склероза [19]. Клиническая апробация клеток пуповинной крови показала безопасность и эффективность в лечении гипоксически-ишемической энцефа-лопатии новорожденных [13], ДЦП [31,56] и ау-тизма [47].…”
Section: Chernykh Er Et Al черных ер и др Medical Immunology (Runclassified